UNIX password security : Ten years later - Feldmeier, David C.
Passwords in the UNIX operating system are encrypted with the crypt algorithm and kept in the publicly-readable file /etc/passwd. This paper examines the vulnerability of UNIX to attacks on its password system. Over the past 10 years, improvements in hardware and software have increased the crypts/second/dollar ratio by five orders of magnitude. We reexamine the UNIX password system in light of these advances and point out possible solutions to the problem of easily found passwords.